2017
DOI: 10.1063/1.4981911
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat sink and source and entropy generation on MHD mixed convection of a Cu-water nanofluid in a lid-driven square porous enclosure with partial slip

Abstract: In this work, the effects of the presence of a heat sink and a heat source and their lengths and locations and the entropy generation on MHD mixed convection flow and heat transfer in a porous enclosure filled with a Cu-water nanofluid in the presence of partial slip effect are investigated numerically. Both the lid driven vertical walls of the cavity are thermally insulated and are moving with constant and equal speeds in their own plane and the effect of partial slip is imposed on these walls. A segment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(58 citation statements)
references
References 43 publications
1
57
0
Order By: Relevance
“…Research on the mixed convection in cavities and enclosures have a five‐decade history. In a wide range of cavity applications like electronic cooling, drying processes, heating and tempering processes, porous media there are natural convection and forced convection it the same time with considerable importance. It seems that the studies of Torrance et al and Ghia et al were the earliest one in numerical research in the field of lid‐driven mixed convection in the cavity.…”
Section: Studies On the Mhd Nf Mixed Convectionmentioning
confidence: 99%
“…Research on the mixed convection in cavities and enclosures have a five‐decade history. In a wide range of cavity applications like electronic cooling, drying processes, heating and tempering processes, porous media there are natural convection and forced convection it the same time with considerable importance. It seems that the studies of Torrance et al and Ghia et al were the earliest one in numerical research in the field of lid‐driven mixed convection in the cavity.…”
Section: Studies On the Mhd Nf Mixed Convectionmentioning
confidence: 99%
“…However, the porous medium and the solid walls are assumed to be electrically non-conducting [4]. The induced magnetic field from the electrically conducting fluid and the Hall effect are neglected [21,22,24]. The induced magnetic field is ignored due to the small value of magnetic Reynolds number, which generally results from partially ionized gaseous substance used as a working fluid.…”
Section: Modeling Aspectsmentioning
confidence: 99%
“…Akar et al [19] have analyzed turbulent fluid flow around a rotating cylinder and evaluated entropy generation. In other classes of works on convection lid-driven cavities have considered porous media with no-magnetic field [20], magnetic fields in the absence of porous substance [20][21][22] and magnetic fields along with porous substrate [16,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the viscosity and thermal conductivity of nanofluids are formulated by a volume fraction and nanoparticle size, then continuity, momentum, and energy equations are solved for nanofluids. In the two-phase model, the volume fraction distribution equation is added to other conservation equations [47][48][49][50][51][52][53]. However, most comparative studies have concluded that the two-phase models predict almost identical hydrodynamic fields to the single-phase ones, but this is not the case for thermal fields.…”
Section: Mathematical Modellingmentioning
confidence: 99%